2009
DOI: 10.1002/jobm.200800364
|View full text |Cite
|
Sign up to set email alerts
|

Efficient inhibition of human cytomegalovirus UL122 gene expression in cell by small interfering RNAs

Abstract: In order to develop a gene therapy to human cytomegalovirus (HCMV), RNA interference (RNAi) was employed to inhibit the expression of HCMV UL122 gene in vitro. Recombinant vector pUL122-EGFP, which expressed UL122-EGFP fusion protein, and recombinant vectors psi122-1, psi122-2 and psi122-3, which expressed small interfering RNAs (siRNAs) targeted to UL122 were contransfected into AD293 cells. The fluorescence signal of pUL122-EGFP was greatly suppressed by psi122-1 and psi122-2, with an inhibitory rate of 82.0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…To our knowledge, no study has considered using one siRNA to simultaneously abolish the expression of multiple IE genes, even though reports have demonstrated that siRNA-mediated targeting of other open reading frames (ORFs) can affect HCMV replication (4,24,68,74,79). A result of this present study is the demonstration that targeting a conserved and shared region of IE genes can inhibit HCMV replication, thereby illustrating the potential of using this region as a new drug target for RNAi-based therapeutics.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To our knowledge, no study has considered using one siRNA to simultaneously abolish the expression of multiple IE genes, even though reports have demonstrated that siRNA-mediated targeting of other open reading frames (ORFs) can affect HCMV replication (4,24,68,74,79). A result of this present study is the demonstration that targeting a conserved and shared region of IE genes can inhibit HCMV replication, thereby illustrating the potential of using this region as a new drug target for RNAi-based therapeutics.…”
Section: Discussionmentioning
confidence: 99%
“…With the ongoing efforts in RNAi-based therapeutic development, small interfering RNAs (siRNAs) and their derivatives have been designed to inhibit the expression of several genes related to virus infections in humans, including those with human immunodeficiency virus type 1, hepatitis C virus, hepatitis B virus, poliovirus, human papillomavirus, and influenza virus (9,31,32,39,52,81), which provides evidence that RNAi has the potential to be an effective strategy to control viral diseases. There are also reports on RNAi-based targeting of HCMV genes (4,22,24,68,74,79).…”
mentioning
confidence: 99%
“…The ΔCq values (Cq gene -Cq β-Actin ) were calculated, following which the ΔΔCq (ΔCq treated -ΔCq control ) were calculated. The relative numbers of HCMV DNAs were described using the equation 2 -ΔΔCq (22). The experiments were repeated three times.…”
Section: Stable Expression Of Nudt14 and Transfection Of Nudt14-specimentioning
confidence: 99%